Do young people in Australian educational systems receive adequate support to feel empowered in engaging with Sustainable Development Goals? - Morley, Sarah (Consilience, 2020)
With the anticipated rise of over double the Paris Agreement’s 2°C goal, climate change is likely to jeopardize the pros- perity of future generations. Thus, it has become increasingly apparent that young demographics must be integrated into the process required to achieve the UN’s Sustainable Development Goals (SDGs) owing to their disproportionately threatened futures over that of adult demographics. A major barrier to children engaging with SDG progress is evident in Australian educational policies, which fail to provide adequate opportunities for young people. Moreover, a lack of individual autonomy in young people can lead to feelings of disempowerment regarding sustainability. Hence, at the present moment, young people in Australian educational institutions are deprived of adequate support systems that could help them feel empowered by contributing to sustainability progress. Research methods undertaken for this paper include literature review, interviews with Australian students and teachers, research into successful international frameworks for youth programs, policy review, and analysis of Australian educational frameworks. Opportunities for empowerment through education and intergenerational support are vital for children to be integrated into the work of SDGs. This fails to transpire within Australian educational institutions. Although there exist various independent organisations which promote tools for youth empowerment throughout Australia, the lack of wider systematic support results in insufficient accessibility for teachers and students alike. Whilst young people possess the capacity to play a role in politically securitising climate change and the achievement of SDGs, supportive systems are required through structural changes, including policy, to initiate progress.